INFLUENCE OF ACCUMULATED FATIGUE DAMAGE ON CRACK PROPAGATION IN ALCLAD ALUMINUM ALLOY - Карускевич, М. В.; Щепак, С. В.; Щур, O. I.; Плащинська, А. В. (Science-based technologies, 2013)
Application of damage tolerance principle at operation of aircrafts assumes ability to predict propagation of fatigue cracks. Conducted experiments have proved that local metal damage accumulated due to cyclic loadings has influence on fatigue crack propagation, especially on the initial stages of crack development. Density of deformation relief at the stress concentrator is being used as damage indicator. It has been proved, that there exists correlation between time of crack propagation and saturation of deformation relief at the stress concentrator.